Quality control of the blood pressure phenotype in the Gaoyou population study. (3rd May 2016) - Lu, Yi-Chao; Li, Shan-Shan; Zhang, Hai-Feng; Odili, Augustine N.; Yao, Wen-Ming; Gong, Lei; Zhou, Yan-Li; Zhou, Fang; Yang, Rong; Sheng, Yan-Hui; Xu, Dong-Jie; Kong, Xiang-Qing; et al.
Abstract: The Korotkoff approach is the only blood pressure (BP) measurement technique that allows contemporary data to be compared with decades of research. We randomly recruited 4483 people (53.3% women; mean age 52.1 years) from Gaoyou County, Jiangsu Province, China. Nine observers recorded the participants™ BP three times consecutively following Chinese Society of Hypertension guidelines. We assessed the BP phenotype based on five criteria: completeness of readings, percentage of identical BP readings, odd BP readings, end-digit preference and trends in BP from the first to the third reading. The proportion of participants with identical readings were 2.0% and 3.1% for systolic (SBP) and diastolic blood pressure (DBP), respectively. Among 26, 898 BP values, 0.3% ended in an odd number. Among observers, the prevalence of identical readings varied from 0% to 5.3% for SBP and from 0% to 6.8% for DBP. Compared with the expected frequency of 20%, those ending in 0 had a lower frequency (17.2%; p < 0.001), whereas those ending in 8 had a higher frequency (22.4%; p < 0.001). From the first to the third measurement, SBP and DBP decreased ( p < 0.001) by 0.87 and 0.55 mmHg, respectively. In conclusion, the procedures set up in the Gaoyou study produced a high-quality BP phenotype.